Nitration of Azasydnones and Azasydnonimines: A Method for the Functionalization of Aryl Derivatives. Issue 7 (5th June 2019) - Dalinger, Igor L.; Serushkina, Olga V.; Lipilin, Dmitry L.; Anisimov, Aleksei A.; Suponitsky, Kyrill Yu.; Sheremetev, Aleksei B.
Abstract: The first example of functionalization of mesoionic 3‐R‐1, 2, 3, 4‐oxatriazol‐5‐ones and 3‐substituted‐1, 2, 3, 4‐oxatriazol‐5‐imines (azasydnones and azasydnonimines, respectively) by the electrophilic reaction without destruction of the oxatriazole ring is reported. Nitration of a range of aryl derivatives bearing various electron donating and withdrawing substituents at the ortho ‐, meta ‐ and para ‐positions using HNO3 /H2 SO4 mixtures has been assessed in order to develop an approach for the synthesis of corresponding nitroaryl derivatives. Whereas nitration occurs meta to the azasydnone ring, the regioselectivity of the electrophilic substitution can be affected by the nature of the substituent attached to the aryl ring, and a variety of polyfunctionalized derivatives can be readily accessed by using this methodology, which may have applications in the target‐oriented synthesis. The reactivity, synthesis, and structure of the mesoionic 3‐substituted‐1, 2, 3, 4‐oxatriazole derivatives described here provide interesting new information on this known but poorly understood heterocycle. Abstract : A great nitration : Insight into the unprecedented functionalization of mesoionic 3‐aryl‐1, 2, 3, 4‐oxatriazoles (known as 3‐arylazasydnones) for preparing previously unavailable nitroaryl architectures is presented. The azasydnone ring is not destroyed under the reaction conditions, thus providing methodology for the synthesis of its multifunctional derivatives suitable for further diversification.